Performance of the automated Sysmex XN-3000 analyser for detecting white blood cell abnormalities in South Africa - Jasmine Ramiah; Dashini Pillay; Nadine Rapiti (AOSIS, 2023)
Background: Automated haematology analysers such as the Sysmex XN-3000 (Sysmex Corporation, Kobe, Japan) utilise white blood cell (WBC) flags to identify quantitative and qualitative abnormalities. Owing to clinical and biological factors, the sensitivity and specificity of the flags vary when compared to microscopy, the gold-standard method for assessing peripheral blood smear (PBS) morphology. Objective: This study assessed the performance of the Sysmex XN-3000 haematology analyser in comparison to PBS microscopy for the detection of WBC abnormalities. Methods: We collected 250 random full blood count samples from the haematology laboratory at Inkosi Albert Luthuli Central Hospital, Durban, KwaZulu-Natal, South Africa, from March 2022 to April 2022. The performance of the automated WBC flags of the Sysmex XN-3000 was assessed in comparison to PBS microscopy, and the impact of established clinical variables on the performance of the flags was determined. Results: The sensitivity of the 'blast' flag was 96.3%, and the specificity was 84.9%. The efficiency of the flag was adversely impacted by low white cell counts ( 1.5 × 109/L; p  0.001), chemotherapy (p = 0.002), malignancy (p = 0.02), and infection (p = 0.02). The 'abnormal lymphocyte' flag demonstrated a sensitivity of 90% and a specificity of 96.2%, and its performance was adversely impacted by chemotherapy exposure (p = 0.03). Three cases (1.2%) erroneously flagged as 'monocytosis' demonstrated blasts on microscopy. Conclusion: In our setting, PBS microscopy remains necessary to confirm blasts, abnormal lymphocytes, and monocytosis in patients with malignancy, current chemotherapy exposure, low white cell counts, and infection. What this study adds: This study adds evidence that PBS morphology remains the gold standard for confirming WBC abnormalities in patients with a history of malignancy, chemotherapy, and leucopenia.